Exploring the antimicrobial and antibiofilm potency of four essential oils against selected human pathogens using in vitro and in silico approaches - Kamal A. Qureshi; Adil Parvez; Humaira Ismatullah; Hanan Almahasheer; Osamah Al Rugaie (PLoS ONE, 2025)
Multi-drug-resistant (MDR) pathogens pose a significant global health challenge, underscoring the urgent need for novel antimicrobial agents with minimal toxicity to humans. This study investigated the in vitro and in silico antimicrobial and antibiofilm potentials of four essential oils (EOs): clove bud oil (CBO; Syzygium aromaticum L.), black seed oil (BSO; Nigella sativa L.), cinnamon bark oil (CNBO; Cinnamomum zeylanicum), and citronella oil (CTLO; Cymbopogon nardus L.), against 19 selected human pathogens, including MDR strains. Among the tested EOs, CBO, BSO, and CNBO exhibited the highest antibacterial activity against Staphylococcus epidermidis, with the mean zone of inhibition diameters (ZIDs) of 20.0 ±  0.2 mm, 46.0 ±  0.3 mm, and 32.0 ±  0.1 mm, respectively, at a concentration of 10 µL/disc, while CTLO displayed no antibacterial activity. CNBO demonstrated superior antifungal activity, with the mean ZIDs of 49.0 ±  0.3 mm and 36.0 ±  0.3 mm for Candida albicans and Aspergillus niger, respectively. Molecular docking analyses revealed robust interactions of key bioactive compounds—eugenol (EU) from CBO, thymoquinone (TQ) from BSO, cinnamaldehyde (CN) from CNBO, citronellal (CIT) and linalool (LIN) from CTLO—with microbial target proteins, substantiating their antimicrobial and antibiofilm potential. Notably, CTLO, despite limited in vitro activity, exhibited unique binding interactions in silico, suggesting potential niche applications. These findings underscore the translational potential of EOs as alternative antimicrobial therapies against MDR infections, particularly biofilm-associated infections, and highlight the need for further in vivo studies to validate their efficacy and safety.